(untitled) - Hartley, John (New York, 1984)
Much has been said and written about Japan's manufacturing prowess. Most ofthe comment comes from people who are merely visitors to the country and can be best cIassified as 'observers looking in from the outside'. Other views come from the Japanese themselves in which the double barrier of culture and language filters out much information that would be of real value to Western industrialists. Neither of these limitations apply to John Hartley, who has been resident in Japan for the past five years. He understands the culture, can speak the language and has extensive contacts at the highest level. Therefore, he is in a unique position to report on the Japanese scene and its activities in advanced manufacturing technology. This he has been doing on a regular basis to IFS magazines: The Industrial Robot, Assembly Automation, Sensor Review and The FMS Magazine. Most of the material in this book is from John Hartley's 'pen' and represents his most significant contributions on flexible automation in Japan to these journals over the last three years. It is augmented with a few other articles written by leading authorities on new technology in Japanese manufacturing industry.
Keywords: Tự động hóa,Automation; Nhật Bản,Japan